From Global Collapse to Recovery : Economic Adjustment and Growth Prospects in Latin America and the Caribbean - World Bank (Washington, DC, 2017)
The global crisis is now in the rear view mirror and world growth is being restored. In sharp contrast with past episodes of global turmoil, this time the recovery is led by the periphery, specifically by the larger and more dynamic emerging markets (Brazil, China, India, South Korea, Malaysia, Philippines, and Thailand). For this group of emerging markets (EMs), the contraction in economic activity was much smaller than that of rich countries, the recovery started earlier, and the rebound has been much steeper. Latin America and the Caribbean (LAC) are second among emerging regions, after Asia, in the strength of the recovery. The first part of the report focuses on macroeconomic and financial aspects, emphasizing the outlook going forward. Finally, the second part examines some aspects of the adjustment in labor markets during this crisis in comparison to previous ones.